EMPLOYABILITY PADA MAHASISWA KEGURUAN DI UNIVERSITAS NEGERI DAN UNIVERSITAS SWASTA - Elsa Tamara Shalsabila; Anissa Lestari Kadiyono (Departemen Ilmu Administrasi Bisnis, Fakultas Ilmu Sosial dan Ilmu Politik, UNPAD, 2019)
Employability means a set of skills, knowledge, understanding, and personal attributes that make an individual more possible to choose and maintain occupations to be satisfied and successful. The low employability of pedagogy students becomes a concern in this study. This study aims to compare employability between pedagogy students in public universities and private universities. The research design used was quantitative non-experimental. A total of 133 public university pedagogy students and 104 private university pedagogy students participated. The data was obtained using two-stage cluster random sampling technique. Comparison of employability between pedagogy students in public universities and private universities was analyzed using Mann Whitney. The result showed there was a significant difference in employability between pedagogy students in public universities and private universities (p <0.05). Employability prediction based on dimensions sequentially were Generic Skills (91.8%), Career Development Learning (81.3%), Experience (67.3%), Degree Subject Knowledge, Understanding, and Skills (60.6%), and Emotional Intelligence (54%). Employability of pedagogy students in public universities was higher than private universities. This is due to differences in the university quality, namely Raw Input and University Accreditation. Employability adalah seperangkat keterampilan, pengetahuan, pemahaman, dan atribut pribadi yang lebih memungkinkan seseorang untuk memilih dan mempertahankan pekerjaannya supaya merasa puas dan sukses. Rendahnya employability pada calon guru menjadi inti masalah di penelitian ini. Tujuan penelitian ini untuk membandingkan employability pada mahasiswa keguruan di universitas negeri dan universitas swasta. Rancangan penelitian yang digunakan adalah non-eksperimental kuantitatif. Sebanyak 133 mahasiswa keguruan universitas negeri dan 104 mahasiswa keguruan universitas swasta menjadi subjek penelitian. Pengumpulan data menggunakan teknik two stage cluster random sampling. Employability pada mahasiswa keguruan di universitas negeri dan universitas swasta dibandingkan dengan menggunakan uji Mann Whitney. Hasil yang diperoleh adalah terdapat perbedaan employability yang signifikan antara mahasiswa keguruan di universitas negeri dan universitas swasta (p < 0.05). Prediksi employability berdasarkan dimensi secara berurutan adalah Generic Skills (91.8%), Career Development Learning (81.3%), Experience (67.3%), Degree Subject Knowledge, Understanding, and Skills (60.6%), dan Emotional Intelligence (54%). Employability pada mahasiswa keguruan di universitas negeri lebih tinggi dibanding universitas swasta. Hal ini disebabkan oleh perbedaan mutu universitas, yaitu Raw Input dan akreditasi universitas.